Let’s Play Politics: Multiplayer Computer Games as a Communicative Political Technology - Daria N. Shlykova; Ilya A. Turkin (RUDN Journal of Political Science, 2025)
Computer games have evolved beyond mere entertainment orescapism, becoming increasingly politicized within contemporary society. This transformation reflects several key trends: the growing number and diversification ofgamers worldwide, the creation ofalternative platforms for cross-border social interactions, and the emergence ofnovel behavior patterns influenced byin-game experiences. Modern forms ofcivic engagement exhibit two distinct characteristics: heightened reliance oninteractive “new media” channels for communicating demands topolitical systems via adual-layered communication framework, alongside aproliferation ofperformative elements-so-called “theatrical practices”-in political discourse. Asintegrated components ofthe metaverse, video games now facilitate the intertwining ofreal-world and digital environments, rendering them influential tools for policymaking. However, this convergence may exacerbate societal tensions due toreduced geographical separation and diminished opportunities for face-to-face dialogue among diverse social strata. Additionally, the inherent nature ofgaming-its playful and simulated aspects-alters ethical norms governing communication, freeing participants from constraints imposed byreality while enabling unusual conduct unseen inconventional settings. Consequently, itbecomes imperative toexplore whether increased regulation ofplayer activities within these virtual domains might emerge over time. Ultimately, though structured similarly toconventional modes ofpolitical involvement, the primary objective remains securing control and maintaining authority inboth online and offline contexts.